Correction to: Impact of Regulation (EU) No. 536/2014 on clinical trial approval processes in two Italian oncology centers - Daniela Bencardino; Fabiana Marchetti; Cristina Mazzi; Marianna Ferrari; Francesca Garibaldi; Giulia Ferrera; Giulia Ponti; Chiara Altavilla; Laura Rossi; Matteo Verzè; Vanda Salutari; Vincenzina Mora; et al. (Journal of Pharmaceutical Innovation, 2026)

Impact of Regulation (EU) No. 536/2014 on clinical trial approval processes in two Italian oncology centers - Daniela Bencardino; Fabiana Marchetti; Cristina Mazzi; Marianna Ferrari; Francesca Garibaldi; Giulia Ferrera; Giulia Ponti; Chiara Altavilla; Laura Rossi; Matteo Verzè; Vanda Salutari; Vincenzina Mora; et al. (Journal of Pharmaceutical Innovation, 2026)

Unlocking the Potential of Marine Sidestreams in the Blue Economy: Lessons Learned from the EcoeFISHent Project on Fish Collagen - Lorenzo Dondero; Giulia De Negri Atanasio; Francesca Tardanico; Erica Lertora; Raffaella Boggia; Vittorio Capra; Agnese Cometto; Mattia Costamagna; Fi.L.S.E; Mirvana Feletti; Fulvio Garibaldi; Federica Grasso; et al. (Marine Biotechnology, 2025)
This review provides a general overview of collagen structure, biosynthesis, and biological properties, with a particular focus on marine collagen sources, especially fisheries discards and by-catches. Additionally, well-documented applications of collagen are presented, with special emphasis not only on its final use but also on the processes enabling sustainable and safe recovery from materials that would otherwise go to waste. Particular attention is given to the extraction process, highlighting key aspects essential for the industrialization of fish sidestreams, such as hygiene standards, adherence to good manufacturing practices, and ensuring minimal environmental impact. In this context, the EcoeFISHent projects have provided valuable insights, aiming to create replicable, systemic, and sustainable territorial clusters based on a multi-circular economy and industrial symbiosis. The main goal of this project is to increase the monetary income of certain categories, such as fishery and aquaculture activities, through the valorization of underutilized biomass.

Induced suppressiveness toFusarium oxysporum f.sp.radicis lycopersici in rockwool substrate used in closed soilless systems - Andrea Minuto; Francesca Clematis; Maria Lodovica Gullino; Angelo Garibaldi (Phytoparasitica, 2007)